The Triple Helix of Digital Engagement: Unifying Technology Acceptance, Trust Signaling, and Social Contagion in Generation Z’s Social Commerce Repurchase Decisions - Bui Thanh Khoa (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
This study investigated Generation Z’s repurchase intention in social commerce environments by integrating three theoretical frameworks: the unified theory of acceptance and use of technology, signaling theory, and herding behavior. The research addressed critical gaps in understanding continued engagement behaviors of digitally native consumers in socially embedded commerce platforms. Data were collected from 542 Generation Z consumers using a structured questionnaire, and relationships were tested using partial least squares structural equation modeling. Results demonstrated that all UTAUT factors significantly influenced repurchase intention. Return policy leniency, as a quality signal, positively impacted repurchase intention both directly and indirectly through enhanced online trust. Fear of missing out demonstrated significant direct effects on repurchase intention and operated indirectly through imitative behaviors. This research advances the theoretical understanding of Generation Z’s continued engagement with social commerce by validating an integrated framework that simultaneously accounts for technological, informational, and social-psychological dimensions. The findings provide practical guidance for social commerce platforms seeking to enhance Generation Z’s loyalty through balanced strategies addressing functional performance, trust-building signals, and social validation mechanisms.